Expressão imuno-histoquímica das integrinas α2ß1, α3ß, e α5ß1, em carcinoma epidermóide de lábio inferior e língua - Pereira, Antonio Luiz Amaral (2006)
The unpredictable biologic behavior of the oral squamous cells carcinoma has determined extensive research on the evolution of such tumor. Due to the existing relation between the outer cell matrix and the tumor cells, the integrins have been used as markers in the predictive study of the cell behavior. This study aims to analyze immunohistochemically the expression of the integrin α2β1, α3β1, and α5β1 connections for the collagen, the laminin and the fibronectin respectively in 15 cases of squamous cells carcinoma from the lower lip and 15 from the tongue, with different scores of malignance grading. A predominantly diffuse, cytoplasm and granular immunological marking was observed in the majority of the analyzed cases. According to the marking intensity, integrin α2β1 appeared positive in 80% of the lip and in 93,3% of the tongue cases. The immunological reactivity of integrin α3β1 was classified as positive in 60% of both the tongue and lip cases. For this integrin, 20% and 33.3% of the tongue and lip cases, respectively, were negative. In relation to integrin α5β1 the intensity was classified as positive in 53,3% of the cases and strongly positive in 46,7% of those located in the lip. In the tongue carcinomas, the intensity was positive in 46,7% of the cases and strongly positive in 53,3%. The statistic analysis did not show any significant differences or correlation of expression between these integrins nor between the anatomical sites or between different scores of malignancy grading. The expressive immunological marking of the integrins, α2β1, α3β1, and α5β1 in the studied cases of squamous cell carcinomas leads us to think of a great participation of these proteins in oral carcinogenesis; however, our results do not allow us to correlate its expression as an indicator of variations in the biological behavior of this neoplasia